Rapid characterization of biotherapeutic proteins by size-exclusion chromatography coupled to native mass spectrometry. Issue 2 (17th February 2016) - Haberger, Markus; Leiss, Michael; Heidenreich, Anna-Katharina; Pester, Oxana; Hafenmair, Georg; Hook, Michaela; Bonnington, Lea; Wegele, Harald; Haindl, Markus; Reusch, Dietmar; Bulau, Patrick
ABSTRACT: High-molecular weight aggregates such as antibody dimers and other side products derived from incorrect light or heavy chain association typically represent critical product-related impurities for bispecific antibody formats. In this study, an approach employing ultra-pressure liquid chromatography size-exclusion separation combined with native electrospray ionization mass spectrometry for the simultaneous formation, identification and quantification of size variants in recombinant antibodies was developed. Samples exposed to storage and elevated temperature(s) enabled the identification of various bispecific antibody size variants. This test system hence allowed us to study the variants formed during formulation and bio-process development, and can thus be transferred to quality control units for routine in-process control and release analytics. In addition, native SEC-UV/MS not only facilitates the detailed analysis of low-abundant and non-covalent size variants during process characterization/validation studies, but is also essential for the SEC-UV method validation prior to admission to the market.